Study on factors that lead to the abandoned building project in Borneo (Sabah & Sarawak) - Izyana Jannati, Sabri (2019)
Housing projects are classified as "abandoned" by the Ministry of Housing and Local Government (MHLG) when there is no activity at the project site, continuously, for more than six months after the expected date of delivery of vacant possession. This is based on the date of the first Sale and Purchase Agreement (S&P) signed between the developer and a purchaser that align together with work contract. Abandonment of housing project is considered one of the most common and serious problems hit the Malaysian construction industry from the number and value of the affected projects. It not only affects buyers directly but also all parties involved with the project as well as the public and the government. Sabah and Sarawak are the two states in Malaysia and housing projects are handled by the Sabah and Sarawak Local Government and Housing Ministry (LGHM) unlike in Peninsular Malaysia which is managed by the Ministry of Housing and Local Government (MHLG). This study wants to explore and collect information toward the factors that lead to the abandoned housing project that occur in Sabah and Sarawak. Objective of this study are to analyse the factors that lead to the abandonment housing project in Borneo (Sabah & Sarawak), to investigate cause and effect of the factors that contributes to the abandoned houses and project, and to propose the suitable solution to overcome the abandoned building project problem. The questionnaire surveys are conducted to collect the data based on likert‟s scale to rank the agreement of the respondent towards the questions in the questionnaires based on Average Index method (AI). As for respondents, they come from the professional field in the construction industry because want to ask for their opinion and advice regarding this study and to give more accurate and precise data. Furthermore, the factors that lead to the abandoned housing project can be categorized as financial difficulties, economic condition, unfavourable government policies, mismanagement and inefficient public delivery system. Lastly, as knowing the cause and effect, the solution to avoid the problem also needed to be proposed. The solution is to save the construction industry from rotten more than now.